Plantar pressure is changed to increase post-impact ball speed during longline forehand and backhand groundstroke in elite female tennis players - Lambrich, Johanna; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2023)
Introduction Achieving high ball speed during the execution of groundstrokes represents a performance-relevant factor in tennis. However, it is unclear how plantar pressure data undergo change during the execution of groundstrokes by tennis players to achieve high postimpact ball speed. Thus, the objective of the present study is to determine how tennis players change the plantar pressure in each foot when they execute longline forehand and backhand groundstrokes in order to increase postimpact ball speed. Methods Seventeen healthy nationally ranked female tennis players (mean age: 21.7 ± 7.7 years) participated in this study. The players performed longline forehand and backhand groundstrokes (topspin) at four postimpact ball speed levels, i.e., at 80 km/h, 90 km/h, 100 km/h, and vmax. Plantar pressure was measured in each foot [i.e., dominant (equals the stroke arm) and non-dominant] using flexible instrumented insoles. Results Irrespective of the stroke technique, the repeated measures ANOVA procedure showed significant ball speed × foot dominance interactions. For the forehand stroke, post hoc analyses revealed significantly increased (dominant foot) and decreased (non-dominant foot) pressure values when the postimpact ball speed increased from 100 km/h to vmax. For the backhand stroke, the post hoc analyses yielded significantly decreased (dominant and non-dominant foot) plantar pressure values when the postimpact ball speed increased from 100 km/h to vmax. There were no further significant differences between the other ball speed levels. Discussion The significantly varying plantar pressure changes depending on the stroke technique and foot dominance to increase postimpact ball speed suggest that specific physical exercises related to the foot (dominant vs. non-dominant foot) and groundstroke (forehand vs. backhand) seem to be necessary for plantar pressure optimization.